São Gotardo-MG, um estudo sobre a presença nipo-descendente no cerrado mineiro - Santana, Luiz Otávio Costa (2015)
The paper is a reflection on the movement of migrant Japanese descendants in São Gotardo, Minas Gerais, especially since the implementation of the Program of Guided Settlement of Alto Paranaíba (PADAP), in the 1970s. Upon its arrival, the city experienced several economic, political, social and especially cultural, changes. To try to understand this process of change that the city experienced and still experiences, it was crucial to focus on a deeper study, based on a focused bibliography aimed at the Japanese ethnic group, the migrant phenomenon and also to studies that deal directly with São Gotardo in the memoirist sense and other areas. From the literature theorizing a ethnographic work was performed in order to understand the elements that are present in the city and that are the result of varied situations. Finally, and not least, interviews were conducted with Japanese descendants and not descendants residents of São Gotardo the main characters involved in numerous processes that took place and are still present in the city. Thus, it seeks to not only think the relevance of nipponic descendant presence in São Gotardo, but also the various Japanese cultural processes that emerged after their arrival and that became the product of the current São Gotardo culture.